True poetry : traditional and popular verse in Ontario - Greenhill, Pauline, 1955- (McGill-Queen's University Press, 1989)
Focusing on the importance of traditional and popular poetry for the poets, the presenters, and the local audience, Greenhill examines the activity of creating and using poetry in a community context. She gives numerous examples of Ontario folk verse, among them twenty-one poems about Canadian runner Terry Fox, whose battle with cancer inspired many folk poets. True Poetry pioneers the examination of folk poetry in Canada and adds to a limited body of scholarship on the topic. It will be of interest to anyone concerned with Canadian society, traditional folklore, and popular culture.